2009
DOI: 10.1084/jem.20082533
|View full text |Cite
|
Sign up to set email alerts
|

Zinc transporter Znt5/Slc30a5 is required for the mast cell–mediated delayed-type allergic reaction but not the immediate-type reaction

Abstract: Zinc (Zn) is an essential nutrient and its deficiency causes immunodeficiency. However, it remains unknown how Zn homeostasis is regulated in mast cells and if Zn transporters are involved in allergic reactions. We show that Znt5/Slc30a5 is required for contact hypersensitivity and mast cell–mediated delayed-type allergic response but not for immediate passive cutaneous anaphylaxis. In mast cells from Znt5−/− mice, Fcϵ receptor I (FcϵRI)–induced cytokine production was diminished, but degranulation was intact.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 67 publications
2
81
0
Order By: Relevance
“…In addition, we and another group reported that Znt5, Bcl-10, and Malt-1 are specifically required for cytokine production by mast cells but not for their degranulation (37,38). These mice should be valuable models for further dissecting the in vivo roles of mast cells in immune and biological responses, as well as for analyzing the pathological process of a variety of immune-related diseases.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we and another group reported that Znt5, Bcl-10, and Malt-1 are specifically required for cytokine production by mast cells but not for their degranulation (37,38). These mice should be valuable models for further dissecting the in vivo roles of mast cells in immune and biological responses, as well as for analyzing the pathological process of a variety of immune-related diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, zinc acts as an inhibitor of cyclic nucleotide phosphodiesterase (PDE), when PDE is inhibited, cyclic nucleotide cGMP (Cyclic guanosine monophosphate) is elevated leading to the activation of PKA (protein kinase A) and subsequent inhibition of NF-κB [43]. Similarly, zinc can bind to a zinc finger-like motif found on protein kinase C (PKC) and inhibit PMA-mediated PKC translocation to the membrane, when this occurs in mast cells, NF-κB activity is indirectly inhibited [44]. Those mentioned studies demonstrates how zinc influences inflammation via NF-κB signalling pathways through several mechanisms and at many levels.…”
Section: A Nf-κb and Other Signalling Pathwaymentioning
confidence: 99%
“…5A), even though these mice showed malfunctions in other tissues and cells. 45,46) Thus ZnT5 is not significantly involved in zinc-insulin crystal formation in cells. Instead, it must be important to the zinc supply into the early secretory pathway in cells, 65) with ZnT6, as described above (see Fig.…”
Section: Pancreatic Cellsmentioning
confidence: 96%
“…Furthermore, it is important to elucidate how the redundant functions and independent functions of zinc mediated by the ZnT5/ZnT6 and ZnT7 complexes are discriminated in the early secretory pathway, because ZnT5 and ZnT7 knockout (KO) mice show somewhat different phenotypes, although these discrepancies can be attributed to the differences in their expression patterns. [45][46][47] ZnT1 is known to locate predominantly to the plasma membrane, 48) but recently it was shown to locate to the ER by forming complexes with EVER proteins in human keratinocytes. The complexes affect intracellular zinc distribution and downregulate transcription factors stimulated by MTF1, c-Jun, and Elk.…”
Section: Survey Of Znts Localized To the Early Secretory Pathwaymentioning
confidence: 99%
See 1 more Smart Citation